Differences of small-scale farmers and the related short agri-food value chains An empirical evidence from Hungary - Zsófia Benedek; Imre Fertő; Lajos Baráth; József Tóth (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
Recently, short food supply chains have been thoroughly studied in some countries; however, data are sparse from others. In Hungary, the local food movement has been developing very fast and an outburst in the number of farmers markets has happened, due to the changes of the legal environment. The paper addresses the question whether farmers selling at various short food supply chains are different based on their socio-demographic, farm- and production-related characteristics, expectations and motivations. Employing survey data our results confirm that short supply chains are different in terms of farmers' profiles. The outcomes are important in the light of the coming EU funding schemes as different small-scale farmers require different supporting frameworks and solutions.
Keywords: Q13; Q18; R58; 330; Short food supply chain; local food system; farmers' market; organic farming